Introducing the Newly Isolated Bacterium Aneurinibacillus sp. H1 as an Auspicious Thermophilic Producer of Various Polyhydroxyalkanoates (PHA) Copolymers-1. Isolation and Characterization of the Bacterium - Pernicova, Iva; Novackova, Ivana; Sedlacek, Petr; Kourilova, Xenie; Kalina, Michal; Kovalcik, Adriana; Koller, Martin; Nebesarova, Jana; Krzyzanek, Vladislav; Hrubanova, Kamila; Masilko, Jiri; Slaninova, Eva; et al. (Polymers, 2020)
Extremophilic microorganisms are considered being very promising candidates for biotechnological production of various products including polyhydroxyalkanoates (PHA). The aim of this work was to evaluate the PHA production potential of a novel PHA-producing thermophilic Gram-positive isolate Aneurinibacillus sp. H1. This organism was capable of efficient conversion of glycerol into poly(3-hydroxybutyrate) (P3HB), the homopolyester of 3-hydroxybutyrate (3HB). In flasks experiment, under optimal cultivation temperature of 45 °C, the P3HB content in biomass and P3HB titers reached 55.31% of cell dry mass and 2.03 g/L, respectively. Further, the isolate was capable of biosynthesis of PHA copolymers and terpolymers containing high molar fractions of 3-hydroxyvalerate (3HV) and 4-hydroxybutyrate (4HB). Especially 4HB contents in PHA were very high (up to 91 mol %) when 1,4-butanediol was used as a substrate. Based on these results, it can be stated that Aneurinibacillus sp. H1 is a very promising candidate for production of PHA with tailored material properties.
Keywords: P(3HB-co-4HB); polyhydroxyalkanoates; P(3HB-co-3HV-co-4HB); Aneurinibacillus sp.; thermophiles